Thermal analysis of polymers : (John Wiley, 2009)
Thermal Analysis of Polymers: Fundamentals and Applications emphasizes the practical uses of thermal analysis, enabling readers to take full advantage of its capabilities as a polymer characterization tool in their laboratories. The book offers essential theoretical background; however, it focuses on how to perform a broad range of thermal analysis measurements and tests, with detailed coverage of methods, applications, instrumentation, and calibration. Moreover, it helps readers correctly interpret their results. This book features a team of authors whose expertise spans all the thermal analysis techniques and applications covered in the book. Their advice is based not only on thorough knowledge of the literature, but also their own hands-on experience working in the lab. Among the topics covered are: Differential scanning calorimetry, thermogravimetric analysis